Menstrual-cycle symptoms and sleep characteristics in elite soccer players - Halson, S. L.; Johnston, R. D.; Pearson, M.; Minahan, C. (International Journal of Sports Physiology and Performance, 2024)
Purpose To determine whether menstrual-cycle symptoms are associated with sleep in elite female athletes.